(untitled) - YEKTININGTIAS (Language Horizon: Journal of Language Studies, 2014)
PI’S RELIGIOSITY IN YANN MARTEL’S LIFE OF PI Yektiningtias English Literature, Art and Language Faculty, State University of Surabaya yektiningtias@gmail.com Drs. Much. Khoiri, M.Si English Literature, Art and Language Faculty, State University of Surabaya Much_choiri@yahoo.com Abstrak Agama merupakan istitusi mengenai ketuhanan. Agama berisi sekumpulan pengertian dan kebiasaan yang mengacu pada individu. Individu tersebut adalah individu yang religius, pernah religius, atau bisa jadi religius. Partisipasi dalam suatu hal yang berbau religius didefinisikan sebagai religiusitas. Individu yang memiliki religiusitas tidak berarti mereka menganut sebuah agama. Selagi mereka melakukan hal hal yang sebuah agama perintahkan terhadap para pengikutnya, seperti percaya kepada Tuhan, mencintai ciptaan Tuhan, dan melakukan tindakan religius, individu tersebut dapat dikatakan religius. Life of Pi, sebuah novel karya Yann Martel, menggambarkan religiusitas seorang anak laki –laki, Piscine Molitor Patel atau Pi. Sejalan dengan hal tersebut, tujuan dari pernelitian ini adalah untuk menggambarkan religiusitas dari Pi dalam hidupnya dan mengungkapkan faktor-faktor yang mempengaruhi religiusitas tersebut. Metode analisis secara tidak langsung berdasarkan teori psikologi remaja karya Frederick Tracy karena sebagian besar novel tersebut menyuguhkan kehidupan Pi ketika dia masih dalam masa remaja. Hasil penelitian menunjukkan bahwa Pi telah memenuhi tiga komponen religiusitas-keyakinan, perasaan, dan tindakan. Terlebih, ada lima faktor yang mempengaruhi religiusitas Pi. Faktor tersebut adalah pengaruh keluarga, pengaruh pekerja professional, kebutuhan, ketertarikan, dan rasionalitas. Kata kunci: agama, religiusitas, komponen religiusitas, remaja Abstract Religion is the institution of godness. It contains a set of meaning and behavior referring to individuals. The individuals are religious, were religious, or could be religious. The participation in religious things is defined as religiosity. Individuals who have religiosity do not mean they commit to a religion. As long as they do what a religion tells its followers to do, like believing God, loving God’s creation, and doing religious action, the individuals are considered religious. Life of Pi, a novel by Yann Martel, depicts the religiosity of a boy, Piscine Molitor Patel or Pi. In line with that, the purpose of this study is to depict religiosity of Pi in his life and reveal the factors that influence it. The method of the analysis indirectly works mostly based on Frederick Tracy’s psychology of adolescence theory because mostly the novel presents the life of Pi when he is in adolescent period. The result of this study shows that Pi has fulfilled three components of religiosity—knowing, feeling, and doing. Moreover, there are five factors that influence Pi’s religiosity. They are family’s influence, professional workers’ influence, needs, interest, and rationality. Keywords: religion, religiosity, component of religiosity, adolescence INTRODUCTION Fiction, by its definition, is describing imaginary events and people. The contents of a prose literature which are included in fiction are drawn from imagination that shows creativity or original thought. An unrealistic plot like a boy who flies by a broom, talking animals, aliens, or monsters that attacks the earth often cause delusion. Thus, an author puts truths to make the work more realistic although as the mentality history, a work of art can be a manifestation of reality, critic of reality, and alternative thought of reality (Supaat, 2008: v). A modern literature has a notion that art or literature is a matter of creativity. Often the creativity is bounded with the legalistic and formalistic doctrines of religion. Thus Western societies put the religion aside from their literature. The literature is free and free from religious matters. On the contrary Y.B Mangunwijaya in Supaat (2004: 175) stated that basically all literatures are religious. T.S Elliot in Supaat (2004: 166) added that the value of literature must be seen from the ethic and religiousness. If there is an idea or agreement of a society of a religious ethic so the literature must be ‘good’ like the religious ethic. Religion within a fiction is based on religious ideas from the real world. The religious ideas can be included into a fictional prose because basically fictional characters are imaginary. Although the characters are made up, they still have people’s same willingness, needs, and drives in the real world. What people do in real world includes seeking religious understandings. (http://altreligion. about.com/od/artandculture/a/Religion-And-Fiction.htm retrieved on March 7th 2013). Based on the explanation, art works often raises religious issues to make the story becomes more real. The issues contain the truths from real religious ideas. The authors put more understanding to the issues from the facts. A character seeks for religious understanding for some reasons. The character may find peace and satisfied feeling towards his or her life in religion. Although religion is a term for conceivable religions whether formal or informal (Ferm, 1959: 647) a character does not always practice what a particular religion that he or she commits’ rules. A satisfaction is found deep inside a feeling. Because it is related to feeling, it can be related to religiosity. Stolz (2009: 347) defines religiosity as what an individual chooses, feels, believes, and acts that refer to a religion that already exists or to a self-made religion. Religion itself is a cultural symbol-system that responds to problems and possibilities that are related to a very important reality. This system influences everyday life and cannot be controlled directly. Stolz continues with religiosity is when an individual prays, sacrifices, believes, loves or fear his god while the religious symbol-system or religions are like Christianity and Islam (Stolz, 2009: 347). An author may put his understanding about religious things to his works. ‘Literature going behind God’ is an effort of a man in letter by his works in which nuances in religious with his total comprehension of faith , so that he could comprehend fully of his seeking of God, his Creator, and literature is a dynamic, productive, and creative media (Supaat, 2004: 176). Yann Martel puts his idea of religion and religious things into his fictional work, Life of Pi. “Pi is interested in religions: so am I. Pi is open to all faiths: so am I. Pi is comfortable in different Godhouses: so am I. There is a sociocultural component to religions. Just as there are different ways of feeding the body, there are different ways of feeding the soul. Each religion is one group of people's attempt to understand ultimate reality. I think in each one there is a portion of truth and a portion of error. So I see in all great religions the same frame of being, only seen from a different perspective.” (http://abcnews.go.com/GMA/Books/story?id=124838&page=5 retrieved on March 7th 2013) Life of Pi mostly presents such unrealistic things and events. The carnivorous trees and an impossible 227 days survival of a boy together with a Bengal tiger floating on a boat in Pacific Ocean seem hard to dissolve by mind. Although these things are in some ways unrealistic, Martel puts Gods and religions ideas into this work. The Author’s Note in the beginning of his novel states that the story comes up from a man named Mr. Patel. Yann Martel, the author of Life of Pi, was in India in searching for inspiration here he met a man in a café who then tells him to meet a man with great story i.e. Piscine Molitor Patel. He then says that the story will make him believe in God. Life of Pi is uniquely presenting its adventurous content with religious values and zoology. Yann Martel was intelligently put those different things into synchronized single unit. The coordination of the true story of Mr. Patel told in first person is incredible. The story begins about Mr. Patel’s education and working life which serve with the fact that he was a student of religious studies and zoology. Then it shifts to his life when he was a boy, son of a zoo owner. In this part, the story provides facts about some animals’ life inside the cage or out there in the wild. The story next progress is story about Pi’s religious life when he was in his teen that reveals his strange religious practice. The 227 days survival in Pacific Ocean on a boat with a Bengal tiger is the next part of this incredible story and it is closed with he is survived. This novel once comes up with controversy of its originality. Some critics come up with their idea that this novel resembles Scliar’s Max and the Cats, a story about a family of German zookeepers sets sail to Brazil. The ship is shipwrecked and only a young man survives after floating at sea with a wild jaguar. This issue then goes down as a discussion between Scliar and Martel done. But Martel had been firstly mentioned Scliar’s name in his Author’s Note part of his book. (http://www.sparknotes.com /lit/lifeofpi/context.html, retrieved on February 12th, 2013). This issue affects the outstanding content of this novel. Some critics, however, still appreciate the novel. This novel makes the reader recalls the story of Ernest Hemingway’s The Old Man and the Sea Yann Martel was an author of seven awards in literature. His first book entitled The Facts Behind Helsinki Roccamatios and Other Stories was a collection of four short stories published in 1993 deals with themes like illness, the anguish of youth, grief, and loss that blend with the lunacy of 20th century history. This book achieved Journey Prize in Canada. Martel’s second book, his first in the form of novel Self published in 1996. This book succeeded to win Chapters/Books in Canada First Novel Award. This novel’s theme was study of sexual orientation and identity. Also Martel was the author of a collection of letters to the prime minister of Canada, What Is Stephen HarperReading? (http://Literature.britishcouncil.org/ yann-martel on 17 oct 2012) After the publication of his novel in 2001 Life of Pi, his name was widely recognized by literature world. This novel was able to win five different awards. In 2001, this novel won Governor General's Literary Award for Fiction in Canada and also Hugh MacLennan Prize for Fiction. A year later, it won Commonwealth Writers Prize in Eurasia Region as the Best Book although it won over the shortlist. Also in the same year, Life of Pi was able to get the Man Booker Prize for Fiction that made him create much of literary splash rather than with his first two books and it also won the Boeke Prize in South Africa. As the recent achievement, Life of Pi has been filmed in 2012 and achieved a great success. Martel’s works have been praised seven different literary awards although his life began with various odd jobs after he graduated for a degree in philosophy in Trent University in Ontario. He ever became a tree planter, dishwasher, and security guard before he committed in writing at the age of 27. Although he began his life with various odd jobs, his decision to write books after that was a right decision. He got praised for his ability to make multi themes and problems that are not common to be bound in to one. For his ability to combine uncommon multi themes and problems, he succeeded to make Life of Pi to become a novel of great combination of religious values, zoology, and adventurous life. As the opening of the novel, it is told that the novel will make you believe in God. This story reveals Pi’s journey of life since he was child until he was mature and graduated from university. This story provides about Pi’s religious life which is strange and it affects his understanding about his life and God’s destiny for him. The combination of religious theme and zoology of the novel is purposely done for enriching Pi’s religious life portraits. Pi is kind of person with maturity in his mind to combine his understanding about God of his religions towards the objects around him although he is still young. As human life is divided into four divisions (Tracy, 1920: 10) in which the first period is the period of childhood. The second is period of youth where this is the period of procreative function to the process of self maturing. The next period is the period of manhood and the last is the period of decay that is being dead. As the character of Pi in Yann Martel’s Life of Pi is in the second period of life, he experiences great things in his religious life. In his adolescence that is ranged from 12 up to 24 years of life, Tracy (1920: 187) points out that, youngsters seek for spiritual meaning in religion as well as from the objects of nature, events, and their relationship with other fellows. Piscine Molitor Patel or Pi is originally a Hindu. He lives in a Hindu neighborhood when he was kid until he is adolescence. His religious practice has become strange when he meets two religious people i.e. a priest and an imam. Thus, this introduction constructs his understanding about other religions, Christianity and Islam. His decision to commit three religions, Hinduism, Christianity, and Islam simultaneously is also influenced by Bapu Gandhi who said that the most important thing is to love God. Pi has a strong love towards God although he is still a young man. Pi is having a disliking towards his biology teacher who does not believe in God’s existence. Pi sees the doubt on the important of religion and the existence of God as just a while. Every man will pass it someday and reach a happy life. Although Pi is still young, he has already experienced his deep feeling about being religious and to religion itself. The feeling creates him to experience religious flaming. This deep religious feeling or religiosity happens in his teen. His religious feeling seems have mutualism with his personality as adolescence. His life whether they are individual or cultural and social more or less influence personality and affect his decision in understanding religions as the way to love God and being a religious on his multi religions practices. This religiosity that is seen from his religion combinations stresses the importance of individual factors, including social background and personal history. Those backgrounds are to build up his mind of committing three different religions at the same time. Thus this study is to reveal the form of his religiosity in the novel and the influencing factors. RESEARCH METHOD The source of this study is taken from a novel by Yann Martel, Life of Pi reprinted and republished in New York in 2012. The data collection is by analyzing the quotations, phrases, dialogues, or monologues in which reveal thought, speech, action, and attitude that reflects the idea of religiosity of the main character, Pi, from the novel Life of Pi. This study of religiosity will be applied by the concept of religiosity with its components, modes, dimension, orientation, and changes that often experienced by people. The religiosity used to determine and explain about the main character Pi issues of religiosity. To analyze the background of his commitment, it is used psychology of adolescence concept that consists of several psychological points of view about relationship between adolescence and family and religious life of adolescence. Close reading of the novel is done first to determine the major issue of it. The major issues are collected and proposed into a topic of the study by seeing the conflict, the monologue, the dialogue in the novel. After the topic is already decided, it is tried to figure out what should be analyzed with the topic. Thus it is collected two statements of problems. There are the depiction of Pi’s religiosity and the factors that influence his religiosity. The next step is searching related information about concept of the topic and to figure it out, it is used religiosity concept and theory of psychology of adolescence for the analysis and the conclusion. CONCEPT OF RELIGIOSITY Religiosity is a concept that has a bound with religion. This concept of religiosity can be defined in some definitions that relate to the religion itself. Supaat (2008: 175) defines religiosity as an aspect which lies inside the deep heart, flaming in the inner heart, personal attitudes which more or less are mystery for the other people, because are based on intimate psychology i.e. universal totality, that includes human’s ratio and feeling, inside the personal being. This religious attitude is pointed on personal side of an individual toward his God, and having attitudes as what God wants. Stolz (2009: 347).continues with religiosity is when an individual prays, sacrifices, believes, loves or fear his god. Religiosity can also be defined as participation in religious rituals, various behaviors, and attitude in group or society by an individual (Theodorson, 1969: 345). Rituals are usually what a religion tells the adherents to do. Whitehouse (2004: 4) explains rituals as actions that have lack of intrinsic meanings although there are possible interpretations or symbolic motivations that may be the background of the rituals. Although these actions are lack of intrinsic meaning, the ordeals are ritualized and the speculation of their significance and meaning are still present. Focusing on implicit motivations of people doing the behaviors has some tactical merits (Whitehouse, 2004:24). The explicit religious concept that ethnographers interpret is often difficult to differentiate that the concept is the interpretation of the ethnographers or the people’s actual explicit religious concepts. The other reason is from the psychological point of view, implicit concepts are better predictors of behavior. The people can also be manipulated to do the actions because they are not consciously aware and will of their response to the stimulus. This leads to explicit reason to do the behaviors instead of the real motivation of them. The explicit knowledge is likely consisting of post hoc rationalization rather than a guide of the motivation for the behavior (Whitehouse 2004: 25). On the contrary, Fazio stated in Whitehouse (2004: 25) says that the conflicts between the implicit concept and explicit concept are not always true all the time. He says that explicit belief can also be a guide to the motivation. People who do the same ritual procedures regularly results in habituation. Those automated habits can make the people to have less reflection of the symbolic meanings of the rituals (Whitehouse, 2004: 6) for example in religious speech. People can be feeling bored of the doctrinal repetition. Rituals are the main things to do in order to get merits and not being sinful. As Tracy (1920: 183) stated that religion involves man’s attitudes towards the Supreme Being without age differences and the main thing is to do positive attitudes towards the Being. To support these, an adherent often does various behaviors like fasting and to behave or keeping his or her good attitude by helping other people and doing good things. God is the invisible but owns the highest power and attitudes towards the Being, as sacred and profane. Durkheim (1915: 37) states that there are two divisions of world. They are sacred in which is the one containing all and profane which is the other all. These are the distinctive characteristics of religious thought. Sacred thing is not only about the personal beings called gods and spirits but a rock, a house, a tree, or anything can be sacred. Profane is what relates to daily life experience of human beings. For example, it is about someone’s attitude that results in sins or the way a religion teaches human being to have a meaningful life by giving charity and helping one another so it will result in man’s goodness. The representations which express the sacred things, the virtues and powers that they have, or the relation with profane things are like beliefs, myths, dogmas, and legends (Durkheim, 1915: 37) As well as Theodorson, Tarigan (2007:11) supports that. The definition of religiosity for him is as the human attitude which comes from God’s blessing. God blesses human to believe in God, to enjoy modest life, to give charity, to help other people, to be lovable, and to be friendly. Because of the participations, behaviors, and attitudes based on particular religion that an adherent must do, sometimes these will cause strain to the adherents. They may feel under pressure because if they are not doing them, there will not be merits that they will get but sins and being afraid of God. God is someone who watches you to see that you behave yourself. (Powell, 1963: 289) The concept of religiosity is also generally accepted as multidimensional phenomenon. The phenomenon happens in the society related, influenced, or caused by many dimensions. The dimensions come from cultural, social, or individual contexts. Religious as the result of practicing and believing religion is also influenced by the religion’s system of beliefs, rituals, and practices. Thus, individual actions are often influenced by the religion. Because of factors like afraid of being sinful person or to be considered as a religious person, adherents may do more than what a religion tells. This actualization of excessive religious, religiosity (Concise Oxford English Dictionary Eleventh Edition), besides to show that they are religious by doing it excessively, it also can be deviated from the real doctrines. It is agreeable that religion has to do with the relationship between man and his Maker or specifically it is the relationship between man’s attitudes towards whatever he believes to be the owner of the highest power in universe (Tracy, 1920: 183). Because of the existence of attitudes, it needs to differentiate religion and religiosity although they bound each other. Religiosity is something that adherents do from what a religion orders. Then, religion defines as follows A religion is a set of meanings and behaviors having reference to individuals who are or were or could be religious. (Ferm, 1959: 647) The statements means that a religion is a container of what an individual must do or must not do either the individual is religious, was religious, or could be religious. Thus, it is only a term that contains all formal or informal religions in the world (Ferm, 1959: 647). Religion is the institution of godness which is unified system of beliefs, rituals, and practices that typically involve a broader community or believers who share common definitions of the sacred and the profane. (freebook.uvu.edu/SOC1010 retrieved on 18th October 2012) Supporting Ferm, Evans (1978: 305) has a definition of religion in which also has relationship between things or power which are uneasy to explain. Because religion freely allows a man to relate himself to the outer power that cannot be explained with science, quality and intensity of man’s religiosity of his religion can be low or high. A man considered himself as religious man not only because he believes on religion , he can be considered as religious without doing religion’s doctrines or a man who does it but is considered as not religious one as explained as follows that it needs a deep understanding to consider a man as religious person or not. To be religious is to effect in some way and in some measure a vital adjustment (however tentative and incomplete) to whatever is reacted to or regarded implicitly or explicitly as worth of serious and ulterior concern. (Ferm, 1959: 647) Supaat (2008: 175) stated that someone who is religious is defined as human being who has serious inner heart, pious, careful, and with deep spiritual considerations. GENERAL COMPONENT OF RELIGIOSITY For the social psychologist, religion has five main facets. They are the ideological or beliefs, the ritualistic or practice, the experiential or feelings, the intellectual or knowledge and the consequential or effects (Watts and Williams, 1988: 10). These facets bound into one dimension of religiosity. On the other hand, Duke (1988) defines the general components of religiosity seen from social psychologist are knowing or cognition, feeling or affection, and doing or behavior. Knowing or cognition is abstract. Knowing about things that are related to religiosity and religions are inside every man’s mind. This is an ideology. The people believe what he believes that the things are true and good for him. Because ideology is only idea in this context in idea of religious things, the only thing that can be seen from this is the realization of this belief in the real world. For example a person believes that a religion is true. People cannot see his belief but can only see how the person shows his belief true religious doings like doing rituals. The feeling or affective is the feeling dimension of religiosity towards the social situations. The social situations contain things that God has created. Human being, animals, plants, goods, or institution are the creation of God. People who have religiosity are feeling grateful of the existence of His creations. Doing or behavior is the action of showing religiosity. This action aims to get positive effect. Religious doings are the realizations of religion as ideology and the feeling towards the God and His creation in the world. The behaviors are like attending religious rituals like servings God as a duty, studying about religion as the feeling to enlarge his knowledge and religiosity to his God, doing charity as the praise for his sufficiency and love feeling towards fellow, and helping the others to tighten the fellowship. In the matter of religious behavior, cognitive scientists more or less ignored the roles of explicit religious ideas and sentiments as the motivations of people doing the religious behavior (Whitehouse, 2004: 24). Boyer stated in Whitehouse (2004: 24) says that people are feeling the compulsion to participate in rituals because the natural environment often produces contaminants so the people use the rituals as the detection of and protection against them. These specializations are actually just normal cognitive systems. Of these components of religiosity, many researchers still hopes for more developed ways to measure religiosity of someone that the participation in institutional religion because there are differences in religious attitudes and experiences between dominations and between different people with the same denomination and there are fact of the equivalency of average attendance figures (Watts and Williams, 1988: 11). Some people may define themselves as religious in some sense although they play no part in organized religion. From a survey on religious scale items from Independent Television Authority Survey stated in (Watts and Williams, 1988: 11), individuals scored high on religiosity because they classified themselves as very religious or fairly religious, are certain that having some religious beliefs lead a good life, without belief in god life is meaningless, religion helps to maintain standard and morals of society, there is God, god watches each person, are very likely to think of god when they are worried or happy, religious belief affected their everyday lives. MODES OF RELIGIOUS INVOLVEMENT Individual participation on religion consists of two modes of religious involvements. Duke, in his journal, states that the modes are personal mode and institutional mode. The personal mode is built of religious beliefs, feelings, and behaviors. These are found in personal and individualized religion. The person accepts doctrinal orthodoxy from the cultural society around (Duke: 1998). In institutional mode, the religious beliefs, feelings, and behaviors are found in formalized and institutionalized religion. This mode accepts them in which related to religious rituals and worship services like in a particular church or other religions. While Duke divides an individual involvement is a religion as personal and institutional mode, the others like Davidson stated in Duke, separates it to private and public modes. RELIGIOUS ORIENTATION People’s interest toward particular religion that makes them religious depends on their own decision. It is whether they are extrinsically or intrinsically oriented (Allport, 1967: 144). Allport’s point of view of extrinsic religious is caused by outer reasons or influence. The reason why an individual is committing religious acts aims in seizing mundane goals like feeling comforted and protected and also is like to get a social status and approval. To measure an individual religiosity based on extrinsic orientation is by seeing the influence given by peers, family members, or professional workers. Durkheim demonstrates how process that influence by society motivates individual action. The only source of life at which we can morally reanimate ourselves is that formed by the society of our fellow beings; the only moral forces with we can sustain and increase our own are those which we get from others. (Durkheim, 1915: 425) It is different from intrinsic orientation which assumed without achieving a mundane goal even self denying quality as the reason of religious involvement. This orientation arises from the goal of the contents of the religious tradition itself. To measure this orientation is by seeing the personality. CHANGE IN RELIGIOUS COMMITMENT AND PARTICIPATION Life events relate to religiosity. Peter Berger stated in Cornwall (1998) states that plausibility structures i.e. family, church, or voluntary organizations and conversations with the others are important and can give influence to religiosity. Because there are many life events that will influence someone’s religiosity, there is chance of the change of his or her commitment and participation in religion. The changes are change in belief and activity over the life cycle, religion disaffiliation and dropping out, religious conversion and reactivation, religious change as personal development. The changing of religious belief and activity can be related to life cycle. Teens or early twenties may have less religious belief and activity than they who are in late twenties or thirties. This changing is caused by several backgrounds like family backgrounds, early socialization, and to developmental issues of adolescence and young adulthood (Albrecht and Cornwall: 1998) In religious disaffiliation and dropping out, an individual decides to not join one organization because she or he chooses to join another or decides to stop his religious involvement in the organization. Even though this is action of switching, it does not mean they loose their religious faith. They only choose the best belief for them. Religious conversion has often been defined as a rather sudden process consisting of new religious insight or experience which leads to greater religiosity on the part of individual involved (Donahue taken from Albrecht and Cornwall: 1998). Supporting Donahue, Starbuck (1900: 21) added that sudden changes of character like from evil to goodness, sinfulness to righteousness, and indifference to spiritual insight or activity. In the adolescent period, the conversion is an awakening. The conversion can happen in many motifs: conversion from private investigation of alternative ideologies to highly social, emotionally arousing experience (Lofland and Skonovd stated in Albrecht and Cornwall: 1998). Starbuck (1900: 49) states that the motives and forces behind the religious awakening is based on the nature of conversion. To study the motives and fears, the people are grouped into their likeness and differences. They are fears, other self-regarding motives, altruistic motives, following out a moral ideal, remorse and conviction for sin, response to teaching, example and imitation, urging and other forms of social pressure (Starbuck, 1900: 49) Religious development changes as the individual goes matures. This maturation process is primarily seen through psychological study without focuses on the impact of normative events like marriage, first job, child bearing, and death (Albrecht and Cornwall: 1998) PSYCHOLOGY OF ADOLESCENCE Adolescence is the second stage of human life. In this stage, adolescents will experience a period of the birth of procreative function until the full maturity of their powers (Tracy, 1920: 10). This stage is begun in the second dozen period of human life. The first dozen period is childhood, the third is manhood and the fourth or the last period is the beginning of decay of the powers until death. In other word, the adolescent period started from the age of 12 years. Supporting Tracy, Goldenson (1984: 17-18) explains further about the beginning of adolescent of girls and boys. He stated that adolescent period of girls is begun when they are 12 until 24 years. Boys have a year later the beginning of adolescence than girls, which is from 13 until 22 years. The period of adolescence is subdivided into two periods but some writers divided it into three. In the three divisions of this period, there are early, middle, and later adolescence. In this division, the beginning of adolescence happens in the four or five first year while the rest divisions follow this. In two divisions, the period of adolescence is subdivided into early and later adolescence. Both are lined when the adolescents are in their sixteen or seventeen years of life. During the period of adolescence, adolescents will experience a period of puberty. Puberty is a period when sexual life is born and it is also the beginning of procreative quality of them. Although puberty will happen to every person, the birth is varied between an adolescent to the other adolescents. This means that an adolescent can have it when he is 12 and the other may have it in his 14. Besides puberty is the birth of sexual maturity, in some civilized people, puberty is a sign of social and religious obligations of individual. … Frequently by some new emphasis on the social and religious obligations of the individual, evidently with a half-conscious recognition of the close association between the racial and the religious life. (Tracy, 1920: 17). The same thing happens to adolescents in Christian Communions. In this community, adolescents are hoped to take new step of their religiousness and begin to take their religious responsibility. This will lead them to the closer and more open relationship with their church. As well as Tracy, Goldenson (1984: 17-18) stated that during this period, adolescence will experience major various changes that have different rates one to the other. The changes include changing of sexual characteristic, body image, sexual interest, social roles, intellectual development, and self concept. Tracy (1920: 18) stated that in the matter of thought and feeling, adolescence is the period of ‘deepening’. The feeling of adolescents will experience a flaming where they will find deepest meaning of things. All experiences of them will make them to interpret them deeper and bound them into a higher thought. In this case Evans (1978: 93) supports Tracy. He explained that in period of operational thinking, adolescents will not face conflict in thought process from the concrete to the abstract form. The adolescents will be aware of logical of basic things and the formulation of hypotheses (Evans, 1978: 93). Thus, they will seek for the logical reasons behind some things, conditions, or situations around them then they began to understand them as something that they have known or purposely introduced when they were kid. The mind of the adolescent reaches out to that which is implicated or involved in the presentation. In a deeper sense than ever before, the mind now takes hold upon the ideal, builds castles, lays plans, and indulges in day dreams, with all kindred psychic adventures (Tracy, 1920: 18) The feeling of adolescents will be richer than when they are children. This will also become actual. The combination of feeling, thought will result of the birth of emotion. Adolescence has primary emotions. They are love, fear, anger, and curiosity. The adolescence does not learn the emotions. The emotions are inborn. Other emotions are built on those primary emotions. Love is a feeling of strong affection or attachment. This emotion makes adolescence concerns for someone or feels delight in an object, person, or situation. This primary emotion builds some secondary emotions like affection, joy, pleasure, and delight. Adolescence will feel alone and insecure without love. Fear is an emotion which ranges from worry. Hurlock stated in Kapunan (1971: 55) categorizes fear into three: fear of material objects, like animals, airplane, elevator; fear of social relationship, like being alone, meeting people for the first time, making a speech; general fear, like poverty, death, darkness, physical incapacity, marriage. Gates and Pressey stated in Kapunan (1971: 56) say that fear has positive values. Fear causes someone to be cautious and careful, thrifty, sober, and the fear prevents one from doing wrong. But, fear also can make one from going a head and can lead to failure. There are three ways to overcome fear. They are forewarning in which the adolescence should be cautioned of something they are afraid of, assurance in which they are told that nothing is to fear, and to live the experience. Some secondary emotions of fear are moods, anxiety, and worry. Anger is an emotion from resentment to rage. This emotion is caused by inability to do or get what is wanted. It may be being teased, treated unfairly, and being bossed. The expressions of anger are like disobedience, resistance, sneers, threats, satire, gossip, or oral attack. This anger also has positive effect. This can make one accomplish more, make one pause and re-examine his practices and limitations. Curiosity is the beginning of knowledge and learning when one starts asking question. This interest or curiosity makes children being aware of the changes around them. This makes their interest aroused. The birth of emotions of adolescence makes the adolescents becoming aware of the combination of those emotions. After that, the action rises. When children’s action is imitative, habitual and automatic adolescents’ action will be less imitative, habitual, and automatic. It will be controlled by the will although it is not fully controlling the action. It is because their intelligence control is spasmodic and intermittent. FAMILY AND ADOLESCENCE Family condition whether it is related to the parents’ attitudes influences the attitude of adolescence. Since many of attitudes or values own by children are well structured in their eight or nine years that are difficult to change, this means the home environment is the primary factor involved in structuring them. Powell (1963: 266) added that although parents have strong role of structuring children’s attitudes and values, the home environment also influences them. It is including children’s observation of his parent’s interaction with each other and with other adults. According to Warnath in Powell (1963: 267) home is the place for children of learning developmental social skill and the desire to participate in activities related to other individuals. THE RELIGIOUS LIFE OF ADOLESCENCE Everyman is basically a religious being. They are capable of religion not at this age or that age. They are always capable of this. Although everyman’s naturally religious, they are not capable of it in the same sense. It is not also the ideas and feelings towards a religion are the same in every man. An immature man does not have the same things as a mature man has of the ideas and feelings. It can be said that child’s capability of religious experience is not the same in form and content as youth’s and adult’s. Since religion is a matter of thinking, feeling, and acting, children who are not mature, they themselves have intellectual power over their feeling and behavior (Tracy, 1920: 186). As long as they are given early introduction to God, their life is genuinely religious (Tracy, 1920: 186) as they easily absorb things around them. Thus, the character of children’s religious life is based on their mental life and this progress. As everyone knows, child absorbs things around him but without the knowledge of his sense. Although the child tries to look deeper about the knowledge he gets from his surroundings, there is not larger degree of understanding that he will get. Although child may comprehend and speak bout the un-sensed for example the unseen and untouched things, there is not understanding about it. They only know that they can see the unseen if they have keener vision and where to look them. During childhood, children are told that God sees them but they cannot see God and God is near to them but they still cannot see God. They may ask such questions but without understanding. Thus, they will be satisfied to any answers given to them. Religion of child and the religion of youth have much in common but there are still features that differ one from another. The religion of youth is more subjectively personal than the religion of children. Religion of children is natural religion but the youth’s is spiritual religion. Youth tries to find spiritual meaning of objects, events, and relationship of human life. Religion influences moral values as well as social attitudes not only for adults but also children and adolescents. Children know about religion early from the one closed to them like from parents. Since the children’s religion is natural, as long as they are given early introduction about this, they will likely be religious. This differs to adolescent. Early introduction to concept of religion that is relationship between God and man often creates conflict in adolescence. They begin to question the concepts they have absorbed (Powell, 1963: 284) because they start to find out the hidden meaning of something, like no children. For in childhood there is a simple, direct response to the impressions of the environment, on the sensori-motor reflex plane, without the possibility of the deeper and stronger emotions, and with a minimum of logical interpretation or critical analysis. In youth this naive outlook gives way by degrees to one in which the subjective elements play a more prominent part, with the simple feelings giving place to the profounder emotions, mere sense-perception being supplemented by the more ambitious processes of cognition, and the instinctive and habitual motor reactions by deliberate choice and higher volition. (Tracy, 1920: 189) Adolescence is an important period of dedication in participation of organized religions in the world even in primitive form (Ferm, 1959: 378). Ferm also states that When the religious nurture of childhood must issue in personal commitment if significant religious maturity is to follow (Ferm, 1959: 378) Tracy (1920: 191) distincts two distinctive features of adolescence’s religion. The first are the experience of intellectual doubts and difficulties whether it is accompanied by emotional tension and upheaval or not. The second is the experience known as conversion. Doubts and difficulties are related to religious questions. As children is very dogmatic which means they greatly absorbs what others say and answer based on questions that they ask, the mind of adolescence begins to criticize that. Ideas which have heretofore dwelt side by side in consciousness without any sense of clash or conflict, may now reveal to the more alert mind of youth certain incongruities and contradictions. (Tracy, 1920: 193) If the adolescence cannot deal with the idea that they have with the reality that they face, there will be conflict which leads to doubts of what they have believed. In some researches stated by Powell (1963: 286) relating to loss of religious interest with adolescent, show that young people do not loose 100 percents the interest of religion but they do not seem feeling satisfied with traditional religious belief and ritual. In this period, he added that confusion seems to happen that may lead to guilt feeling. Family environment which is included attitudes of father and mother influences the development of young people’s religious attitudes, Parents often give their children with strict adherence to specific religion. This habit can make confusion to the children when they come to a more liberal home (Powell, 1963: 286). However, children with less religious even irreligious parents will make them insecure and envy of seeing their classmates involved in religious experience denied them. A better point of view of religion will be in the attitudes of children whose parents are religious and liberal. These combinations seem to make result in developing more mature religious views (Powell, 1963: 288). According to Allport cited in Powell (1963: 290) religious sentiments occur from needs, interests, temperament, rationality, and cultural response. Young people seek for new experiences, awareness of the presence of God, to be useful and unselfish, to participate responsibly, and become members of a wholesome fellowship (Powell, 1963: 291) Kuhlen and Arnold cited in Powell (1963: 289) agrees that religious beliefs become increasingly abstract with the increase of age. The more age he has, the more likely he becomes religious. For many adolescents, leaving religious practice is temporary since they will enter their adulthood that makes them likely to become affiliated with religious practice. DEPICTION OF PI’S RELIGIOSITY Three general components of religiosity are depicted by Pi. The depictions are Pi’s knowing about God’s existence, knowing about religion, feeling grateful of animals’ existence, grateful of goods’ existence, Pi’s doing like serving God through personal prayer, committing three religions, loving the fellow, and loving animals. As adolescence, Pi has knowledge about the great power of God. Pi thinks that it is only a very serious disease that will kill God. What is meant by serious disease is a real serious disease that infects a human being. Pi thinks that God, the Supreme Being who has super power over all things in the world will not die or never dies because of thing like suffering disease like a man can. God is the creator of human being and all other creatures in this world. He disagrees with his teacher’s opinion that God died during partition in 1947. He might also die during the war or when he was in orphanage. Pi believes and knows it so he thinks that it is an impossible thing for God to die that way like a human being does. He also thinks that if God’s existence in a man’s heart is dead, this condition will lead to terrible things. In other words this is a very dangerous condition. Pi states this because he does not want God disappears from every human being’s heart. He compares the terrible things that will happen because of that condition with terrible disease. He attempts to say that the effect of both things towards human beings and other creatures in the world is vey dangerous. Someone who suffers a not-dangerous disease still can infect the people around him then imagine if the disease is terrible. This will have greater effect towards them. Then, if someone does not recognize his God anymore, this will make destruction. For example, if human beings are the highest God’s creature compared to animals and plants do not have God inside their minds then the God’s blessing like mercy towards the other will be lessen and the worst is disappearance of that. If the people do not have mercy anymore, they will damage the environment. Relating this to Pi’s life that is closed to animals, Pi knows and believes that by keeping God inside his heart will make the world and its contents peaceful. Pi has a positive point of view of religion. For him religion is light. The light will guide human beings to the right way along their life’s way. When Pi met his teacher, Mr. Kumar at his father’s zoo, Pi was so happy to see him there. Mr. Kumar said that he often went to the zoo and thought that other people might think that it was his temple although he was indicating to the Pit of goats’ and rhinos’ cage. He later talked about politic that lead to religious debate between him and inside Pi’s heart. Mr. Kumar thinks that the world will be peaceful if the politicians are like the goats and rhinos. But the real condition is reversed. Pi does not know anything about politics although his parents often complained about Mrs. Gandhi. He bluntly said that religion would save them. After Pi mentioned that they will be saved by religion from the political condition that was terrible, Mr. Kumar’s response was not very good. He admitted that he did not believe in religion. He thought that religion is darkness. He thought that there were no grounds for believing thing like that. He only thought that religion was a superstitious bosh. He did not believe in God’s existence. Hearing this Pi was only thinking that Mr. Kumar was only testing him for his knowledge of religion. He thought that he was like purposely saying that mammals lay eggs. After that Mr. Kumar is an atheist was in his mind. He was then surprised when he was told that God may have died somewhere some when. Although he was surprised of this, Pi did not hate the fact that Mr. Kumar is an atheist but Mr. Kumar’s agonistic made Pi upset. Mr. Kumar spoke that God never came when he needed Him. When he was Pi’s age, he was racked with polio. The God never came and saved Him but the medicine did. Pi did not respond anything about it although it was a bit much for him. Pi chooses not to argue with Mr. Kumar not because of his anger but more afraid of loosing someone he loved. The depiction of Pi’s gratefulness of animals’ existence is found when he was in the zoo. Pi’s father was the owner of a zoo in Pondichery. He was feeling very happy of growing up in a zoo. Almost every animal in the zoo left an impression to Pi. In some case, Pi did not have to depend on his activity to the mundane thing like alarm clock for example. Pi did not have to have the clock because he could use the voice of animals around him to wake him up, to remind him for breakfast. He used the roar of a pride of lion who usually roar off between five-thirty and six every morning. The loud voice of howler monkeys punctuated his breakfast time. The animals in the zoo also give Pi a happy feeling. Besides from his mother’s gaze, he also got a benevolent from bright-eyed otters, burly American bison, and also orang-utans. Pi was living his life as prince who had the fondest memories of living in a zoo because of the animals. The animals brought him advantages. From morning until dark, Pi was always welcomed by them. Every animal in the zoo has different characteristics, habits, and action. There are animals which voices are very disturbing but there are animals which are not. The habits or the actions of the animals whether they are annoying or not, has brought him to think that they are the graceful gifts from God. Seeing their action made Pi feeling as a lucky boy. Pi has always been feeling grateful of what God has given to him. Once when he is in trouble when floating on the Pacific Ocean, he finds goods that will make him survive. Although he is in trouble, he still remembers about the relationship of the goods’ colour with one of the religions he has committed. In Hinduism, saffron is the most sacred color for the Hindu. This color represents fire and symbolizes purity. Wearing this color symbolizes the quest for light. If this color is related to what Pi finds in the lifeboat, this means the goods are source of light for Pi. The light is his survival from the fear. The boat makes him safe from the Pacific Ocean beneath him and the tarpaulin separates him with his Bengal tiger. At first, Pi does not think that the goods he has found will become his lifesaver. But, he then thinks that with the lid, he is separated from Richard Parker. This means he is protected from carnivore that is in the same boat with him. He is feeling grateful of that. Then if the tiger is managed to attack Pi from below, he should push the lid and it will warn him and make him fell backwards to the water. And here it is the function of the lifebuoy. The existence of the goods has caused joyful feeling for Pi. He even cannot compare them with all giving occasions that he has experienced before even the occasions bring great pleasure. Although Pi is floating on the Pacific Ocean, he still does prayers. Pi does the religious rituals adapted to the circumstances. He does all three religions rituals he commits. Pi still does the prayers because he has felt that doing prayer will bring him comfort. But, in practice, doing prayer is very hard for him. He thinks that to have faith in God is difficult. He has to have an opening up, trust, and act of love towards God. It is because he is not in a save condition. There are dangerous problems that he faces on the ocean. He sometimes fills with anger, desolation, and weariness. He is angry at the God who puts him in this kind of situation. In that kind of situation, Pi ensures himself that everything around him is God’s, even the hat he is wearing, the attire, the cat, the ark, the wide acres, the ear. Pi has a very strange religious practice. Although he is still adolescence, he has already practiced three different religions. They are Hinduism, Christianity, and Islam. At the age of fourteen years old, Pi meets Jesus Christ and becomes a Christian although he was born Hindu. He is admired by the God’s Son’s sacrifice. He willingly sacrifices Himself for the goodness of humanity. He pays the humanity sins. The reason is because of love. Although Pi is a Hindu, he also commits to Christianity. He does both Hindu and Christian prayers even right after becoming Christian. Pi commits to Islam a year later. Again he is introduced to Islam by a professional worker. He is a Sufi who is a Muslim mystic. His name is Satish Kumar, person with the same name as his biology teacher. Pi is attracted to Islam because of the brotherhood and devotion that are told in Islam. Pi also feels good when he brings his forehead to the ground. He feels a deep religious contact then. After all those introductions to new religions, Pi practices all of them. Pi’s love toward the fellow is depicted through his relationship with his biology teacher. Although Pi is born Hindu and is a well-content Hindu, he still respects anyone who does not have the same faith with him including his biology teacher, Mr. Satish Kumar. One day Pi sees Mr. Kumar in the zoo. He is a regular visitor of the zoo. When he is visiting zoo, he always reads labels and descriptive notices of every animal. He feels scientifically refreshed after visiting the zoo. In the zoo Mr. Kumar and Pi have a talk about political things in India. Mr. Kumar imagines if they have politicians like two rhinoceros and a goat, that live together in harmony that they are watching, India would not have faced many problems. Then Pi says that religion will save them. Mr. Kumar’s response is out of Pi’s mind. He thinks religion is darkness and God does not exist. Pi is surprised about this. Pi only thinks that he is testing him. But it is not. Mr. Kumar is an atheist, someone who does not believe in God’s existence. Although Mr. Kumar’s point of view about religion and God is not the same as Pi’s, he still accepts this. He only thinks that anyone has doubt like Christ who ever doubts God for forsaking Him. Pi still makes Mr. Kumar as the reason he choose zoology as one of his major in university. Because he is the first atheist person that Pi meets, he is able to think that atheists are his brothers and sisters. He considers Mr. Kumar as a person of blood-relationship with him no matter what faith he has. The faith is their faith. They are free for it like Pi himself. Pi’s love towards animals has made him to become a vegetarian. When Pi is in trouble finding the source of food on the boat on Pacific Ocean, he is finding many flying fish, Dorado fish, have flown into the lifeboat. He is finding this event as happy event because Richard Parker has had some food supplies to fill its hungry stomach. Pi also takes one of the fish. He covers the fish with blanket in order to not make him hurt. After that, he tries several times to kill the fish but he could not complete the action. Pi cannot make it because he feels pity of the fish. He even feels a bit responsible of the rat’s death because he threw it to Richard Parker. To kill the fish, he thinks that he is between the affection feeling towards animals and the need to have meal. In his lifetime, he is a vegetarian. When Pi has been succeeded in killing the fish, the tears come down his cheeks. He cannot feel the life fighting anymore. He feels sad knowing that there is blood on the fish. Although fish is a common animal that human even other animals eat and they rarely think that the fish is a creature that has soul, Pi’s aware that there is soul inside the fish. He is very sorry toward the soul living things that he has killed. The fish cannot enjoy its life anymore. Pi thinks the fish and him are the living creation of God. They should not kill each other. Because he loves it, he is feeling guilty. Then, he promise to pray for the fish in his prayer. FACTORS INFLUENCING PI’S RELIGIOSITY The religiosity of a person can be begun since early life of that person. This can appear to the mind of people when they are children. Not all people will experience religiosity since in their early age. Usually the forms of religiosity are based on religion. The moral values and social attitudes of the people will be likely influenced by it. Early introduction of religious things to people are mostly from the people around them but this religiosity can also come from inside the individuals. The factors that influence religiosity of Pi are family’s influence, professional workers’ influence, needs, interest, and rationality. Pi’s religiosity comes from the influence of his parents because they are the closest figure for the children. Although Pi is from Hindu family, he defines his father as person who does not have strong belief about religion. He later explains that all new animals in the zoo owned by his father are blessed by priest. In the zoo there are also two small shrines. They are to Lord Ganesha and to Hanuman. But, the reason behind this is only to please the zoo director. His father thinks the existence of the shrines is good for his business to build a better relationship with the public, not personal reason like personal salvation for him. It is true that Pi is religious because he has been falling in love with Hinduism. But, the children’s mental life grows. Pi sees his father as a less or lesser religious than him. Then he might think that committing two new other religions is okay for him. Because of this reason, he begins to think it won’t be any problem with my family if I commits to these new religions. Besides of the religious life of his father, Pi also feels that when he was kid, he has never prohibited reading comic and other papers that contain anything about gods of any religion. Pi thinks that his mother was pleased to see him reading any books so long it was not naughty, because she herself is a big reader. Professional workers have a great influence towards Pi’s religiosity. Pi was originally a Hindu because he was born in Hindu family. During his childhood, he was familiar with everything about Hinduism. Later on when he enters his adolescence period that is in his fourteen years old, he begins to know about Christianity. Pi is on a holiday trip in Munnar. In Munnar there are three hills. The hill on the right has a Hindu temple, the hill in the middle has a mosque, and the left hill has a Christian church. Pi is a school boy who attends a Christian school but he never goes inside a church. Then, because of curiosity he decides to hide around a corner of the rectory of the church because he is afraid. Inside the church he sees a figure, a priest who is sitting quietly and patiently waiting for anyone who wants to talk to him. On the next day he manages to enter the church and is welcomed by the priest, Father Martin. Pi thinks he is very welcoming. In that church he was told some story about Christianity including God’s son who was willing to pay the humanity sins. Pi cannot accept this. He always questions this thing to Father Martin. He always answers it is because of love. Pi does not feel satisfied of the answer. On his last day in Munnar, Pi decides to come to the church again. At first he thinks that the priest is not in but he is. He says to Father Martin that he wants to be a Christian. He says that Pi already is. Before Pi leaves, he finds Father Martin smiling to him. It is the smile of Christ for him. From these, Father Martin’s patience and kindness to give explanation to Pi and answers his questions too have made Pi to feel that Christian is not as what he thinks as people with great violence. He has seen the sincerity of Father Martin. He is feeling comforted about what the man is telling. These makes him understands about the religion and finally commits in it. Another professional worker that influences Pi to Pi’s religiosity is an imam of a mosque in Mullah Street. At that time, Pi is also in his adolescent period. He is sixteen years old when he knows Islam. Pi actually does not have good impression about Islam. Islam has a reputation worse than Christianity. Islam has fewer gods but greate